Why Does the Law Matter? Investor Protection and Its Effects on Investment, Finance, and Growth - MCLEAN, R. DAVID; ZHANG, TIANYU; ZHAO, MENGXIN (Journal of Finance, 2012)
ABSTRACT Investor protection is associated with greater investment sensitivity to q and lower investment sensitivity to cash flow. Finance plays a role in causing these effects; in countries with strong investor protection, external finance increases more strongly with q , and declines more strongly with cash flow. We further find that q and cash flow sensitivities are associated with ex post investment efficiency; investment predicts growth and profits more strongly in countries with greater q sensitivities and lower cash flow sensitivities. The paper's findings are broadly consistent with investor protection promoting accurate share prices, reducing financial constraints, and encouraging efficient investment.